(3cJGH HQSdjS aj JOHjQ GdQLd defRdIs - (3HQSdjSs
(3ChdgG (B:s
(3bGd Ef CeQ GdefRd jJe HCQHY NUGd ChdgG GdeGd hGdKGfi GdMOI hGdKGdK GdeQCI hGdQGHY GdhdO s
(3BNQgG (B:s
(3hdYdg jYQa aVjdI Pdc ai hbJ dGjecfg ajg JdGajg hESJOQGc eG aGJ efg ajMUd Edi GdfOGeI aEf GdjSjQ ef GdNWC ai ChGFd GdCTjGA hCUhdgG djS HjSjQ hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3CNdGb (B- (3JjehQ (B291) s
Keywords: (3GdadSaI hGdefWbs